2015
DOI: 10.1097/grf.0000000000000133
|View full text |Cite
|
Sign up to set email alerts
|

Benign Tumors and Tumor-like Lesions of the Vulva

Abstract: A variety of mass lesions may affect the vulva. These may be non-neoplastic, or represent benign or malignant neoplasms. A review of benign mass lesions and neoplasms of the vulva is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 17 publications
0
39
0
1
Order By: Relevance
“…The differential diagnosis of a solid growth the Bartholin's gland include leiomyoma, primary carcinoma, and leiomyosarcoma and other vulvar mesenchymal lesions such as cellular angio broma, angiomyo broblastoma and aggressive angiomyxoma. (22)(23)(24). Leiomyosarcomas of the vulva are very rare, thus frequently mistaken for benign Bartholin's gland lesions, which delays the diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The differential diagnosis of a solid growth the Bartholin's gland include leiomyoma, primary carcinoma, and leiomyosarcoma and other vulvar mesenchymal lesions such as cellular angio broma, angiomyo broblastoma and aggressive angiomyxoma. (22)(23)(24). Leiomyosarcomas of the vulva are very rare, thus frequently mistaken for benign Bartholin's gland lesions, which delays the diagnosis and management.…”
Section: Discussionmentioning
confidence: 99%
“…The Bartholin's cyst is less painful but may cause local discomfort and often associates with history of recurrent Bartholin's abscesses. A recent systematic review found that there is no current randomised trial evidence to support the use of any single surgical intervention for the treatment of a symptomatic cyst or abscess of the Bartholin's gland (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
“…Granular cell tumours usually present as solitary, pale lesions that are slow growing and are relatively painless. The differential diagnosis would be Bartholin's gland tumour, sebaceous cyst, lipoma and papilloma [3]. Histologically, granular cell tumours are found in the dermis and the main morphological feature is the granularity of the cytoplasm, which is caused by massive accumulation of phagolysosomes.…”
Section: Discussionmentioning
confidence: 99%
“…Histologically, the skin appears thin with loss of the crevices found between the nipples. Surface skin is vitrified, and a set of chronic inflammatory cells is observed beneath it [48][49][50][51][52][53].…”
Section: Squamous Cell Hyperplasiamentioning
confidence: 99%